Retribution - Kenyon, Sherrilyn (New York : St. Martin's Press, 2011)
Brought together by an angry god and chased by ancient enemies out to kill them both, hired gunslinger William Jessup Brady and orphaned vampire-raised Abigail Yager must find a way to overcome their mutual hatred or watch as one of the darkest of powers rises and kills both the races they've sworn to protect.
Keywords: Vampires; Assassins; Gods & goddesses; Werewolves; Roman; Paranormal romance stories; Fantasy fiction; Love stories